If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24 = 24k Solving -24 = 24k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-24k' to each side of the equation. -24 + -24k = 24k + -24k Combine like terms: 24k + -24k = 0 -24 + -24k = 0 Add '24' to each side of the equation. -24 + 24 + -24k = 0 + 24 Combine like terms: -24 + 24 = 0 0 + -24k = 0 + 24 -24k = 0 + 24 Combine like terms: 0 + 24 = 24 -24k = 24 Divide each side by '-24'. k = -1 Simplifying k = -1
| 6(x+2)(x+2)-5(x+2)=1 | | .02+(159.96+1s)=5s+79.98 | | 45x-23x-12x= | | 5x^2+5x=8 | | 9(k+2)-8(k+6)=7 | | X+10-7x=4 | | 7-6v=5v+29 | | 7h+4=8+6h | | 11-(3x-6)+2(4x+5)-x=0 | | A=zv+z | | 9-3x-5x=81 | | 7h+5=8+6h | | 0=4s^4-17s^2+4 | | 2+(4p+1s)=5s+2p | | (2x+4)(2x+4)-2(2x+4)+1=0 | | -7-2x+6x=-39 | | A=yt+y | | -7(n-6)=98 | | n-1.3n+1.8=1.5n-1.8 | | 4x^2+32x-60=0 | | -7x-(-7-3x)=-9 | | 6=x+x-6 | | -7h+4=16-8h | | 3p-16p=7+2(-8p-3) | | 3s^2-21s-180=0 | | -2h^2+11h+21=21 | | -(8x+2)=-(1+2x) | | 2y+5y=7 | | (5x+1)(5x+1)-12(5x+1)+36=0 | | 1-3x=2x+18 | | -5(x+4)=-8x-22 | | -6+t=-4 |